Diabetic Ketoacidosis in a Patient with Type 2 Diabetes After Initiation of Sodium–Glucose Cotransporter 2 Inhibitor Treatment. Issue 2 (11th September 2015) - Storgaard, Heidi; Bagger, Jonatan I.; Knop, Filip K.; Vilsbøll, Tina; Rungby, Jørgen
Abstract: Sodium–glucose cotransporter 2 inhibitors (SGLT2i) were recently introduced for the treatment of type 2 diabetes (T2D). SGLT2i lower plasma glucose by inhibiting the renal reuptake of glucose leading to glucosuria. Generally, these drugs are considered safe to use. However, recently, SGLT2i have been suggested to predispose to ketoacidosis. Here, we present a case of diabetic ketoacidosis (DKA) developed in an obese, poorly controlled male patient with T2D treated with the SGLT2i dapagliflozin. He was admitted with DKA 5 days after the initiation of treatment with the SGLT2i dapagliflozin. On admission, the primary symptoms were nausea and dizziness, and he was hypertensive (170/103) and tachycardic (119 bpm) and had mild hyperglycaemia (15.3 mmol/l), severe ketonuria and severe metabolic acidosis (pH 7.08). He responded well to infusions of insulin, glucose and saline and was discharged after 72 hr with insulin as the only glucose‐lowering therapy. After 1 month, dapagliflozin was reintroduced as add‐on to insulin with no recurrent signs of ketoacidosis. During acute illness or other conditions with increased insulin demands in diabetes, SGLT2i may predispose to the formation of ketone bodies and ensuing acidosis.